Communication in times of crisis. The specificity of effective communication with voters of modern, market-oriented political organizations - Sempach, Marek (Koszty współczesnych kryzysów, 2021)
The purpose of this paper is to verify the key indirect instruments of effective communication of MOP’s (Market Oriented Parties) on political marketplace in Poland. MOP’s are the modern political organizations that use contemporary marketing activities to gain the competitive advantage. Furthermore, article aspires to verify the hypothesis that only modern market oriented parties may provide the effective communication by use of appropriate marketing tools. In accordance to the analysis performed and sources criticism including the observation, the author has reached the conclusion and overthrown the selected hypothesis.